Clinical Features and Treatment Outcome of Pediatric Acute Promyelocytic Leukemia in Combined Military Hospital, Dhaka - Islam, Md Azizul; Nahar, Kamrun (Bangladesh Armed Forces Medical Journal, 2024)
Background: Acute promyelocytic leukemia (APML) is a relatively rare blood disease in children that is highly curable with current treatment strategies. It is a distinct type of AML characterized by chromosomal translocations involving the retinoid acid receptor (RAR-A) gene on chromosome 17. It accounts for 20-25% of all AML cases. The aim of this study was to describe the diagnostic features of pediatric APL and the result with ATRA and ATO based protocol. Methods: It was a descriptive type of cross-sectional study with purposively selected 10 newly diagnosed APML patients treated in the Pediatric Oncology unit of the Department of Pediatrics in CMH Dhaka during the period of 2018 to 2022. Diagnosis of all patients were done by aspirating bone marrow morphology and cytogenetic t(15:17) or t(11:17) transcript. Informed written consent was taken from parents. Data were collected by semi-structured questionnaire and analyzed by Statistical Package for Social Sciences (SPSS version 25). Results: Among 10 respondents median age was 4.2 years with female predominant (60%). Most common clinical presentations at diagnosis were fever (100%), bleeding manifestations (100%), Hepatomegaly (90%) bony tenderness (90%), splenomegaly (70%), and lymphadenopathy (70%). Almost all the patients had low Hb & low platelet count & WBC were variable. Cytogenetic analysis revealed 90% had PML/RARA positive & 30% had FLT3/ITD positive. All of these patients were treated with trans-retinoic acid (ATRA) based treatment, which led to 80% cases ATRA syndrome. Other common toxicities noticed febrile neutropenia (50%), severe headache (30%), hyperpigmented skin (10%), pseudotumor cerebri (10%) and others. There were 10% relapse cases, which later proceeded to relapse protocol and were in remission. The remaining 90% of patients were alive and in remission until the last day of follow-up. Conclusion: With ATRA-based treatment overall survival is good achieved remission and only 10% of patients developed relapse. Bangladesh Armed Forces Med J Vol 56 No (2) December 2023, pp 1-9